Open versus endovascular repair of abdominal aortic aneurysm: Incidence of cardiovascular events in 632 patients in a department of defense cohort over 6-year follow-up. (June 2015) - Thomas, Dustin; Anderson, David; Hulten, Edward; McRae, Fiora; Ellis, Shane; Malik, Jamil A; Villines, Todd C; Slim, Ahmad M
Background: Abdominal aortic aneurysm (AAA) is common with unacceptably high rates of mortality and morbidity with unknown rates of complications after repair in the Department of Defense (DoD). Methods: All patients treated at a DOD or VA clinic or medical facility with a diagnosis of AAA identified by ICD-9 code search were identified by Patient Administration Systems and Biostatistics Activity (PASBA) using the Standard Inpatient Data Record (SIDR) and Composite Ambulatory Patient Encounter Record (CAPER) from January 2006 till December 2011. The primary outcome was death, myocardial infarction (MI), stroke, and cardiac arrhythmia between subjects who underwent endovascular aortic repair (EVAR) or open aortic repair (OAR). Results: A total of 8314 patients were screened to identify 632 patients who underwent surgical repair of non-ruptured AAA. EVAR was performed in 497 patients (78.6%) and OAR in 135 patients (21.4%). Mortality at 30 days was less common in EVAR patients (1.6% vs. 6.7%, p  = 0.004), but was not sustained (16.9% vs. 17.8%, p  = 0.797). Mean survival free from mortality was not different between the two groups (EVAR vs. OAR: 6.14 ± 0.13 years vs. 6.11 ± 0.22 years, p  = 0.378). The composite endpoint of MI, stroke, arrhythmia, or death was not different between groups at 30 days (EVAR vs. OAR: 12.9% vs. 14.1%, p  = 0.774) or in long-term follow-up population (EVAR vs. OAR: 40.6% vs. 31.9%, p  = 0.073) though there was a trend toward higher event rates in the EVAR. The composite endpoint of MI, stroke, and arrhythmia occurred in 198 patients (31%). Conclusion: EVAR was associated with lower 30-day mortality rates; however, this benefit was not sustained in longer-term follow-up. There is no difference in the rates of stroke, myocardial infarction, or cardiac arrhythmia at 30 days or in long-term follow-up.